Sửa đề : \(B=x^5+x-1\)
\(=x^5-x^4+x^4-x^3+x^3-x^2+x-1\)
\(=x^5-x^4+x^3+\left(x^4-x^3+x^2\right)-\left(x^2-x+1\right)\)
=\(x^3\left(x^2-x+1\right)+x^2\left(x^2-x+1\right)-\left(x^2-x+1\right)\)
=\(\left(x^3+x^2-1\right)\left(x^2-x+1\right)\)
Bạn chép sai đề rồi :)))
Có sai đề đâu mà chữa: \(==#\)
\(x^5+x+1\\ \\ =x^5+x+1-x^4+x^4-x^3+x^3+x^2-x^2\\ \\ =\left(x^5-x^4+x^2\right)+\left(x^4-x^3+x\right)+\left(x^3-x^2+1\right)\\ \\ =x^2\left(x^3-x+1\right)+x\left(x^3-x+1\right)+\left(x^3-x+1\right)\\ \\ =\left(x^2+x+1\right)\left(x^3-x+1\right)\\ \)